PENGARUH KEPEMIMPINAN, MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJAPEGAWAI DAN DAMPAKNYA PADA KINERJA DINAS PERTANIAN KABUPATEN PIDIE - Boihaki Boihaki (Jurnal Sains Riset, 2019)
The purpose of this study was to determine: (1) how leadership, motivation, discipline, employee performance and the performance of the Department of Agriculture Pidie District (2) the influence of leadership, motivation, self-discipline on the performance of employees, (3) the influence of leadership, motivation, self-discipline on the performance of the Office Agriculture Pidie district (4) the effect of an employee's performance against the performance of the Department of Agriculture Pidie and (5) the effect of leadership, motivation, discipline to employee performance through performance Pidie District Agricultural Office. This research was conducted at the Department of Agriculture Pidie district by the number of respondents as many as 125 people. As for the object of this study is to show that leadership, motivation, discipline, employee performance and the performance of the Department of Agriculture Pidie district already well underway, leadership, motivation and discipline either simultaneously or partially influence employee performance, leadership, motivation and discipline both simultaneously and partially also affect the performance of Pidie District Agricultural Office, employee performance directly affect the performance of the Department of Agriculture Pidie and leadership, motivation and discipline indirectly affect the performance of Pidie District Agricultural Office through the performance of employees. Keywords : Leadership, Motivation, discipline, Employee Performance and Organizational Performance